Planiliza lauvergnii (Eydoux & Souleyet, 1850), a senior synonym of Planiliza affinis (Günther, 1861) with a re-evaluation of keeled back mullets (Mugiliformes: Mugilidae) - Hasan, Mohammad Eusuf; Hasan, Ariba; Béarez, Philippe; Shen, Kang-Ning; Chang, Chih-Wei; Tran, Thanh Thi Viet; Golani, Daniel; Al-Saboonchi, Azhar; Siddiqui, Pirzada Jamal Ahmed; Durand, Jean-Dominique (Zootaxa, 2022)
The taxonomic status of the keeled back mullets (Teleostei: Mugilidae) has been reinvestigated. Two nominal mugilid species having keeled backs from East Asia: Mugil lauvergnii Eydoux & Souleyet, 1850 and Mugil affinis Günther, 1861 have been re-evaluated through examination of the holotypes and fresh specimens. Comparison of morpho-meristic characters of the holotypes shows that both species are identical. Phylogenetic analysis based on mitochondrial cytochrome c oxidase 1 (CO1) confirmed morphological data by highlighting presence of a single clade from East Asia. Mugil lauvergnii (=Planiliza lauvergnii) is thus the sole keeled back mullet from East Asia and a senior synonym of Mugil affinis (=Planiliza affinis). The taxonomic status of two other keeled back mullets, Planiliza carinata and P. klunzingeri, is also contentious due to their similar morphology. Meristic and morphometric variation as well as sequence divergence between the two species are limited but phylogenetic analyses delineate well-supported clades consistent with biogeography and currently accepted taxonomy. Planiliza carinata and P. klunzingeri share a recent common ancestor in a Maximum Likelihood tree, with separate distribution ranges while P. lauvergnii formed a paraphyletic lineage. Based on present findings, we suggest maintenance of the taxonomic distinction of P. klunzingeri and P. carinata and discuss its evolutionary significance.